Prolonged-Release Melatonin for Sleep Disturbances in Autism Spectrum Disorder - Eva Arias Vivas; Adrián García Ron; Elena González Alguacil; Marta Bote Gascón; María Teresa de Santos Moreno; Elsa Santana Cabrera; Guillermo Ruiz-Ocaña de las Cuevas; Juan José García Peñas; Rafael Sánchez-del Hoyo; Víctor Soto Insuga (Annals of Child Neurology)
Purpose Patients with autism spectrum disorder (ASD) often present with sleep disturbances. We evaluated the effectiveness of pediatric prolonged-release melatonin (PedPRM) in real clinical practice, focusing on a population of complex neuropediatric patients with highly refractory insomnia in Spain. Methods The patients were aged 2 to 18 years, diagnosed with ASD, had sleep maintenance insomnia and/or early morning awakening insomnia, and were refractory to prior therapy. The starting dose of PedPRM was 2 or 5 mg (increased to 10 mg, if necessary). Evaluation at 6 months consisted of a sleep diary, the Sleep Disturbance Scale for Children (SDSC), the Pediatric Daytime Sleepiness Scale (PDSS), and the Clinical Global Impression Scale of Improvement (CGI-I) and Severity (CGI-S). Results The median age of the 23 patients was 11.0 years, 56.5% were male, 73.9% had epilepsy, and 78.3% had intellectual disability. One patient discontinued treatment. The mean total sleep time did not change significantly. PedPRM improved sleep latency (median 30.0 to 15.0 minutes; P=0.001) and reduced the number of nocturnal awakenings (median 3.00 to 1.0; P<0.001). PedPRM significantly improved PDSS scores (14.6±4.5 to 10.4±3.5; P<0.001) and SDSC total scores (75.1±12.9 to 61.6±10.9; P<0.001). The CGI-I scale improved in 73.3% of patients; 46.7% of patients were normal, borderline, or mildly ill per CGI-S scale at the end of treatment. Conclusion In real clinical practice, PedPRM significantly improved sleep parameters in patients with ASD who were heavily medicated for comorbidities and were highly refractory to other insomnia treatments.